Post‐Synthetic Decoupling of On‐Surface‐Synthesized Covalent Nanostructures from Ag(111). Issue 27 (29th April 2016) - Rastgoo‐Lahrood, Atena; Björk, Jonas; Lischka, Matthias; Eichhorn, Johanna; Kloft, Stephan; Fritton, Massimo; Strunskus, Thomas; Samanta, Debabrata; Schmittel, Michael; Heckl, Wolfgang M.; Lackinger, Markus
Abstract: The on‐surface synthesis of covalent organic nanosheets driven by reactive metal surfaces leads to strongly adsorbed organic nanostructures, which conceals their intrinsic properties. Hence, reducing the electronic coupling between the organic networks and commonly used metal surfaces is an important step towards characterization of the true material. We demonstrate that post‐synthetic exposure to iodine vapor leads to the intercalation of an iodine monolayer between covalent polyphenylene networks and Ag(111) surfaces. The experimentally observed changes from surface‐bound to detached nanosheets are reproduced by DFT simulations. These findings suggest that the intercalation of iodine provides a material that shows geometric and electronic properties substantially closer to those of the freestanding network. Abstract : The go‐between : Post‐synthetic exposure of covalent porous polyphenylene networks synthesized by on‐surface polymerization on Ag(111) to iodine vapor leads to detachment through intercalation of a densely packed iodine monolayer. Consequently, the organic nanostructures become decoupled from the strongly interacting metal surface, as evident by changes in both the geometric and electronic structures toward freestanding networks.